Temporo-frontal disconnection impairs visual-visual paired association learning but not configural learning in Macaca monkeys. - Gutnikov, SA; Ma, Y; Gaffan, D (1997)
Cynomolgus monkeys were tested in two computer-controlled visual associative memory tasks. The monkeys chose between visual objects on a screen by touching one. In the configural learning task one correct object and one wrong object were presented in each trial. Each of these two objects was composed of two coloured alphanumeric characters abutted together. The designation of the objects as 'correct' or 'wrong' followed a configural rule: e.g. if AB and CD are correct objects then AD and CB are wrong. In the paired association learning task in each trial three spatially separate objects (single alphanumeric characters) were presented. The central object was an instruction cue and the designation of the side objects as 'correct' or 'wrong' choices followed a paired association rule: e.g. if A, C and B are presented (C in the centre) then A is correct and B is wrong; however, if A, D and C are presented then C is correct and A is wrong. Disrupting the direct cortico-cortical interaction between the inferior temporal cortex and the prefrontal cortex by uncinate fascicle transection led to a learning deficit in the paired association task but not in the configural task. These results suggest that the uncinate fascicle facilitates visual-visual associative learning only in the specific case where a visual object acts as an instruction cue to guide the conditional choice of another, spatially separate object, and they support the evidence for a specific role of the uncinate fascicle in the learning of conditional tasks with visual instruction cues.